Megathrust Disaster Mitigation Education For Elderly Women At The Banda Aceh City Seudati Aisyiyah Elderly Daycare: Edukasi Mitigasi Bencana Megathrust Pada Perempuan Lansia Di Daycare Lansia Seudati Aisyiyah Kota Banda Aceh - Hayati Hayati; Ani Darliani; Wirda Wirda (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
This community service project aimed to provide megathrust disaster mitigation education to elderly women at the Seudati Aisyiyah Elderly Daycare in Banda Aceh, a region highly vulnerable to earthquakes and tsunamis. Elderly participants were targeted due to their limited mobility, cognitive challenges, and higher social vulnerability, requiring a specialized approach to disaster preparedness. The preparation phase included site surveys, scheduling coordination, and development of educational materials tailored to the elderly’s needs. The program involved lectures using visual aids, interactive question-and-answer sessions, and open discussions that encouraged active participation. Evaluation results indicated an increased understanding among participants regarding early warning signs of megathrust earthquakes, simple evacuation procedures, and the importance of mental preparedness. The elderly showed strong enthusiasm during the sessions and actively shared experiences, strengthening solidarity and ownership of the learning process. The findings confirm that disaster mitigation education delivered with an empathetic approach, simple language, and appropriate media effectively enhances the resilience of elderly individuals as active participants in disaster risk reduction. Similar programs are recommended to be conducted regularly with the involvement of families, local health cadres, and communities to systematically strengthen the elderly’s capacity for disaster preparedness and evacuation.